Let us be realistic: The impact of perceived brand authenticity and advertising image on consumers’ purchase intentions of food brands - Loebnitz, Natascha; Grunert, Klaus G. (International journal of consumer studies, 2022)
There is a consensus that for a brand being perceived as authentic is an asset. However, an authentic brand is only half of the equation, as a brand must also appear in advertisement that seems authentic. Drawing on the selective accessibility model (SAM), this paper examines in the context of food brands (a) the joint effect of perceived brand authenticity and advertising images on consumers’ purchase intentions toward the advertised food product; (b) the mechanism that drives consumers’ purchase intentions, in which perceived similarity functions as a mediator; and (c) the moderating function of role overload in these relationships. Two studies employed a 2 (advertising image: ideal vs. authentic) × 2 (perceived food brand authenticity: inauthentic vs. authentic) between subjects design. Study 1 (USA) used a manipulation to determine high versus low authentic food brands (fictitious brands), whereas Study 2 (Germany) used actual food brands that consumers perceive to differ in terms of authenticity. Results confirm that brand authenticity serves as an asset. However, the interacting effect of perceived brand authenticity and advertising image is qualified by overall brand evaluation. In line with SAM, participants perceived similarity of one’s own situation with the adverting image depicting “family dinner” situation serves as mediating variable. The results provide insights into when and why food brand marketers should employ authentic advertising images and how they can target those consumers who are more prone to respond positively to authentic ads.